2018
DOI: 10.12659/msm.905979
|View full text |Cite
|
Sign up to set email alerts
|

Association of APOE Gene Polymorphisms with Cerebral Infarction in the Chinese Population

Abstract: BackgroundApolipoprotein E (ApoE) is a multifunctional protein that plays an important role in lipoprotein metabolism. However, the relationship between APOE gene polymorphisms and cerebral infarction in the Chinese population remains unclear. Therefore, we studied the role of APOE gene polymorphisms in patients with cerebral infarction in a Chinese population.Material/MethodsThis study involved 906 patients with cerebral infarction and 1,141 individuals without cerebral infarction who served as controls. APOE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…In the Chinese population, the predominant genotype is E3/ E3 in the Chinese population, whereas the most common allele is E3, followed by E2/E3, E3/E4, E2/E4, E4/E4, and E2/E2. [23][24][25] Our research also confirmed that E3/E3 and E3 were dominant. However, in this research, the E3/E4 genotype follows the E3/E3 genotype in WML group and brain atrophy group, respectively, but the E2/E2 genotype follows the E2/E3 genotype in the co-occurrence of WML and brain atrophy disease group.…”
Section: Discussionsupporting
confidence: 79%
“…In the Chinese population, the predominant genotype is E3/ E3 in the Chinese population, whereas the most common allele is E3, followed by E2/E3, E3/E4, E2/E4, E4/E4, and E2/E2. [23][24][25] Our research also confirmed that E3/E3 and E3 were dominant. However, in this research, the E3/E4 genotype follows the E3/E3 genotype in WML group and brain atrophy group, respectively, but the E2/E2 genotype follows the E2/E3 genotype in the co-occurrence of WML and brain atrophy disease group.…”
Section: Discussionsupporting
confidence: 79%
“…The risk of CI may vary according to the presence of various genetic and environmental factors. In addition, the relationship between the functional variation of multiple gene in different ethnic groups and CI risk has been studied, including the polymorphisms of interleukin-6 gene [2], βfibrinogen gene [3], PON1 hypermethylation and PON3 hypomethylation [4], 5-lipoxygenase-activating protein gene association (ALOX5AP) [5], the cytochrome P450 1A1 (CYP1A1) gene [6], the human scavenger receptor class B type I (SR-BI) gene [7], genes associated with lipid metabolism [8,9], and others [10]. In general, it is important for both risk prediction and prevention of CI by identifying genetic risk.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that ApoE E4 allele is an independent risk factor for T2DM and coronary heart disease [12], but the correlation between ApoE and cerebral infarction is controversial. Some studies have pointed out that ApoE E4 allele is the genetic marker of cerebral infarction [13,14], and other studies have suggested that ApoE E3/E3 and E3/E4 genotypes have protective effects on cerebral infarction in Chinese males rather than females [15].…”
Section: Discussionmentioning
confidence: 99%